Analisis Produksi Ayam Penyet Doa Ibu dalam Perspektif Islam - Suharni Banurea, Mesi; Agustina, Della; Nina Afrina, Kayla; Muthia, Ira; Amelia, Rizqa (Comit: Communication, Information and Technology Journal, 2024)
The production of ayam penyet means there is a high demand for this food in society, especially among Muslims. Ayam Penyet is a typical Indonesian dish consisting of dry fried chicken served with rice, chili sauce and vegetables. From an Islamic perspective, the importance of applying Islamic production principles in the business of ayam penyet arises for several important reasons, namely adherence to Halal Principles: Islamic Religion oblige Muslims to eat halal food. In the production of ayam penyet, applying Islamic production principles ensures the use of halal raw materials, including chicken slaughtered according to sharia-compliant methods. Fairness in Transactions: Islamic production principles encourage fair and honest business practices. In the ayam penyet business, applying Islamic production principles means maintaining fairness in transactions with suppliers, customers and employees, avoiding fraud, and respecting the rights of all parties involved. Product Quality: Islamic production principles encourage producing high quality products. In the ayam penyet business, the application of Islamic production principles involves selecting quality raw materials, processing them properly, and ensuring that the resulting product meets the standards of hygiene and palatability expected by consumers. belief in Muslim consumers that the food they consume meets halal requirements. This is important in building trust and expanding market share among Muslim consumers. The purpose of the analysis of ayam penyet production in an Islamic perspective is to understand the extent to which Islamic production principles are applied in the business, as well as to identify the benefits and challenges associated with implementing these principles. Islamic production. The scope of the analysis includes aspects such as the selection of halal raw materials, production processes, workforce management, product quality, halal labels, and environmental sustainability efforts implemented in the ayam penyet business. Through this analysis, it is hoped that it can be better understood how Islamic production principles contribute to the success of the ayam penyet business, and how the application of Islamic production principles can be further enhanced or integrated to optimize profits and positive impact on the stakeholders involved in the business.